Control loops card rhythm men and women with neurological disorders, connected with stress - O A Butova (RUDN Journal of Medicine, 2013)
Defined that in males with neurological disorders associated with stress in the regulation of cardiac rhythm the autonomous circuit dominates. Females with neurologic pathology of heart rate regulation connect the third level of the center loop that characterizes intersystem homeostasis of cardio-respiratory system. Analysis of the lipid profile in men and women with neurological disorders revealed the significant increased level of low-density lipoprotein. Perhaps the accumulation of low-density lipoprotein particles, and thus the increase of their concentration in blood of patients with neurological disorders, caused by defect of low density lipoprotein receptors. In addition, peripheral muscarin-like action of acetylcholine, which manifests itself in the changing of the homeostatic properties of the endothelium, increased binding to low-density lipoproteins, leads to elevation of cholesterol fraction in the peripheral blood.